Karakteristik Fisikokimia dan Organoleptik Bolu Berbasis Terigu-Garut (Maranta arundinacea) dengan Fortifikasi Bubuk Daun Kelor (Moringa oleifera) : Physicochemical and Organoleptic Characteristics of Wheat-Arrowroot (Maranta arundinacea) Based Yeast-Leavened Cake Fortified with Moringa Leaf Powder (Moringa oleifera) - Devi Fitri Astuti; Bunga Aisyah Nugrahini; M. Handan Afrizal (Universitas Djuanda, 2026)
The high dependency on wheat imports and the increasing demand for functional foods have driven the utilization of local carbohydrate sources such as arrowroot flour (Maranta arundinacea) and antioxidant-rich ingredients like Moringa leaf powder (Moringa oleifera). This study aimed to optimize the formulation of a yeast-leavened cake based on wheat-arrowroot composite flour fortified with Moringa leaf powder and to evaluate its effects on physicochemical and organoleptic characteristics. The research was designed using a Factorial Completely Randomized Design (CRD) with two factors: the proportion of arrowroot flour (0%, 25%, 50%) and the concentration of Moringa leaf powder (0 g, 2 g, 4 g). The results indicated that the interaction between the two factors significantly influenced (P < 0.05) all parameters. The optimal treatment was obtained from the G2K2 formulation. This product exhibited the highest expansion ratio of 81.50%, characterized by the softest crumb structure and uniform porosity. Chemically, the G2K2 sample possessed a pH value of 7.15, a moisture content of 23.20%, and very strong antioxidant activity, with a Radical Scavenging Activity (%RSA) reaching 88.30%. Organoleptically, the G2K1 formulation was the most preferred by panelists (score 5.00/Very Liked); however, G2K2 maintained good acceptability with the added advantage of higher functional value. In conclusion, the combination of arrowroot flour and Moringa powder is capable of producing a cake that is not only superior in texture and sensory attributes but also holds potential as an antioxidant-rich functional food.